2008
DOI: 10.1007/s00122-008-0919-8
|View full text |Cite
|
Sign up to set email alerts
|

A grapevine (Vitis vinifera L.) deoxy-d-xylulose synthase gene colocates with a major quantitative trait loci for terpenol content

Abstract: Linalool, geraniol, nerol, citronellol and alpha-terpineol are isoprenoid molecules responsible for specific aromas found in grapes and wines. Total concentrations (free and bound forms) of these compounds were measured in the skins of mature berries during 2 successive years in two progenies obtained from Muscat Ottonel and Gewurztraminer selfings. Partial genetic maps based on microsatellite markers were constructed and several quantitative trait loci (QTLs) related to terpenol content were detected. A major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 39 publications
6
102
1
Order By: Relevance
“…Jennings (1988) suggested fruit were more aromatic in warm, dry areas than in mild and humid regions. Grape linalool and geraniol contents from mapping populations also showed significant differences in successive years (Duchêne et al 2009). …”
Section: Raspberry Ketonementioning
confidence: 96%
See 2 more Smart Citations
“…Jennings (1988) suggested fruit were more aromatic in warm, dry areas than in mild and humid regions. Grape linalool and geraniol contents from mapping populations also showed significant differences in successive years (Duchêne et al 2009). …”
Section: Raspberry Ketonementioning
confidence: 96%
“…Both of these pathways, the cytosolic mevalonic acid (MVA) pathway and the plastid methylerythritol 4-phosphate (MEP) pathway, produce IPP and DMAPP which are transformed into monoterpenes geraniol and linalool by their respective synthases. In grape, a 1-deoxy-D-xylulose 5-phosphate synthase (DXS) gene from the MEP pathway co-localises with a major QTL for linalool, geraniol and neriol (Battilana et al 2009;Duchêne et al 2009), suggesting the MEP pathway is the major route to monoterpene production. In raspberry, QTL for these monoterpenes are located on different linkage groups: geraniol on LGs 2 and 5 and linalool on LGs 1 and 6 (Fig.…”
Section: Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, we demonstrated that crossing RI and GW can generate a large genetic variability. Genotypes ripening almost as late as Grenache can be expected from such progenies, and we can potentially breed a new variety that reproduces the wine characters of the parents using molecular markers (Duchêne et al 2009a). On the other hand, this variability does not seem sufficient to compensate for the effect of climate change after 2050.…”
mentioning
confidence: 99%
“…The route to the functional characterization of the genetic basis of aroma in grapevine starts with two simultaneous reports demonstrating the colocalization of a grapevine 1-deoxy-d-xylulose 5-phosphate synthase (VviDXS) gene with a major QTL for terpenol content in LG 5 [11,53]. Moreover, by the analysis of the nucleotide diversity and linkage disequilibrium within the VviDXS gene, and testing for association between individual polymorphisms and Muscat flavor in different genetic backgrounds, Emanuelli et al [54] identified significant single nucleotide polymorphisms.…”
Section: From Qtl Mapping To Gene Functionmentioning
confidence: 99%